PENGARUH KUALITAS PRODUK, IKLAN, DAN, CITRA MEREK (BRAND IMAGE) TERHADAP KEPUTUSAN PENGGUNAAN TOLAK ANGIN (STUDI KASUS PADA PENGGUNA TOLAK ANGIN DI KOTA SEMARANG) - Martha Sriningsih Kabaressy; Handoyo DW (Universitas Diponegoro, 2017)
This research is caused by the development of Medicinal herbs business especially “jamu” which is still needed by the people of Indonesia. This phenomenon characterized by many brands of herb medicines such as Tolak Angin, Antangin, Bintang Todjoe etc. Tolak Angin still become market leader in Indonesia marked by top position on Top Brand Index in 2014 – 2016. This research’s purpose is to know the influence of quality products, advertising, and brand image of tolak angin, The type of this research is explanatory research, with data collection techniques through The questionnaire and the interview. Using the technique of sampling with purposive sampling dan accidental sampling. Sample in this research were 100 respondent consists of Tolak Angin Users in Kota Semarang. The Technique to collect data in this research through the questionnaire and interview. This research uses qualitative analysis technique and quantitative analysis technique. Quantitative analysis use validity test, realibility test, correlation coefficient, simple and multiple regression analysis, determination coefficient, signification test that Being tested use SPSS for Windows. The results showed that there are positive effect of quality products to using decisions, positive effect of advertising to using decision, positive effects of brand image to using decisions; quality products, advertising, and brand image has a positive impact using decisions.Based on the research cause advices for the quality of the product Tolak Angin’s composition more adjusted to the needs of users in overcome, on the Tolak Angin packaging expected furnished in a saving manner to keep Tolak Angin that not easy to break, and change the composition to be saver for users although Tolak Angin has given the warning behind the packaging. Advertising Tolak Angin on television or other media become clearer and fuller, and The Tolak Angin Advertising should add more values the advantage with create The unique advertising compared to similar products so as to be more to remember and the information become clearer. Brand image of Tolak Angin is good but have to be improved a healthy lifestyle with drink medicines herbs so the user perceptions to Tolak Angin brand image more better in terms of lifestyle users.